Correlation between different Scheimpflug-based lens densitometry analysis and effective phacoemulsification time in mild nuclear cataracts - Faria-Correia, Fernando (2018)
To assess the correlations between preoperative Scheimpflug-based lens densitometry and effective phacoemulsification time (EPT) in age-related nuclear cataracts.